2017
DOI: 10.1111/ggi.13212
|View full text |Cite
|
Sign up to set email alerts
|

Health and social factors associated with a delayed discharge amongst inpatients in acute geriatric wards: A retrospective observational study

Abstract: The present results are consistent with previous reports that delayed discharges in older hospitalized patients are mainly related to new formal social care requirements in survivors of acute illness. Frailty was an independent risk factor for delay, but its effect might have been confounded by the unmeasured variable of informal care requirements. Our operational definition of delayed discharge does not mirror the legal definition of delayed transfer of care in England, and the results are not externally vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 22 publications
2
27
1
Order By: Relevance
“…Our findings of the association between those who were discharged to places other than their usual residence are consistent with previous studies [ 18 , 19 ]. The National Audit Office [ 10 ] estimated that about 1.15 million bed days were lost due to delayed transfers of care in acute hospitals during 2015 (up 31% since 2013) and found that 54% hospitals in their survey reported that discharge planning did not start soon enough to minimise delays for the majority of older patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings of the association between those who were discharged to places other than their usual residence are consistent with previous studies [ 18 , 19 ]. The National Audit Office [ 10 ] estimated that about 1.15 million bed days were lost due to delayed transfers of care in acute hospitals during 2015 (up 31% since 2013) and found that 54% hospitals in their survey reported that discharge planning did not start soon enough to minimise delays for the majority of older patients.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the discharge destination, the most frequent (77.8%) was long-term care providing rehabilitation, convalescence and palliative care. In up to 6.6% of cases, the patient died during the delayed stay, which is similar to other studies that found the proportion of deaths to be 4.4% [29]. However, this was a lower rate than a report by Meschi et al, which found rates of 16.3% for bed blockers in a long-term unit [31].…”
Section: Discussionsupporting
confidence: 84%
“…In this context, it is likely that clinicians wait for a bed to become available before declaring that a patient is medically fit or ready for discharge, thus prolonging the supposedly appropriate stay and falsifying the delayed stay. Because of this, it is important to record the clinically fit date, as well as the discharge date, in the patient records [29]. To evaluate and compare the efficiency of different hospitals throughout Spain, for example, the average length of stay (ALOS), is an important outcome variable which should be considered using Data Envelopment Analysis (DEA) programming methodologies to optimize input and output variables.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of six studies used fixed values such as: a LOS greater than 30 days (Barba et al, 2015;Kozyrskyi, De Coster, & St John, 2002;Lang et al, 2006), LOS greater than 10 days (Dent & Perez-Zepeda, 2015;McAlister & van Walraven, 2019), and, in one study LOS was categorized as low (< 8 days), intermediate (8-13 days), and high (> 13 days) (Beauchet et al, 2013). Finally, in eight articles, the actual LOS was compared with a relative value such as a hospital stay exceeding the diagnosis-related group LOS (Lang et al, 2006;McCusker, Cole, Dendukuri, & Belzile, 2003), the Healthcare Resource Groups (HRG)-predicted LOS by physical and cognitive function score (Carpenter, Bobby, Kulinskaya, & Seymour, 2007), not being discharged more than 24 hours after last time deemed clinically fit in a medical note (Moore, Hartley, & Romero-Ortuno, 2018), being two standard deviations above the mean (Foer, Ornstein, Soriano, Kathuria, & Dunn, 2012), being in the 75th percentile of the LOS distribution (Antonelli Incalzi et al, 2001), or being in the 90th percentile (Brousseau et al, 2019) greater than the fifth quintile limit (Lisk et al, 2019). Unfortunately, in the remaining studies, the criteria used for these assessments were not described in detail.…”
Section: Assessment Of Los or Ddmentioning
confidence: 99%